Answered

If f(x) = 49- x and g(x) = 7-, which is the rule of the function (8-3)(x)?
a
-x2 - X+ 56
b. x? - 7x2 - 49x + 343
7+X
d. x2 + x +42
C.
Please select the best answer from the choices provided
A. B. C. D.

If f(x) = 49- x and g(x) = 7-, which is the rule of the function (8-3)(x)? a -x2 - X+ 56 b. x? - 7x2 - 49x + 343 7+X d. x2 + x +42 C. Please select the best ans class=

Answer :

Answer:

B ) x³ -7 x² -49 x +343

 (f .g) (x)  = x³ -7 x² -49 x +343

Step-by-step explanation:

Explanation:-

Given f(x) = 49 - x²  and g(x) = 7-x

  (f .g) (x)  = f(x) .g(x)

  (f .g) (x) = ( 49 - x² ) (7-x)

              = 49 ((7-x))- x²(7-x)

             = 343 -49 x -7 x² + x³

 (f .g) (x)  = x³ -7 x² -49 x +343

Conclusion:-

(f .g) (x)  = x³ -7 x² -49 x +343

Other Questions